2006
DOI: 10.1530/rep.1.01125
|View full text |Cite
|
Sign up to set email alerts
|

Successful transplantation of bovine testicular cells to heterologous recipients

Abstract: While heterologous germ cell transplantation was successful in pigs and goats, autologous transplantation alone has been reported to result in donor-derived spermatogenesis in cattle. The objective of this study was to investigate whether the transplantation of heterologous germ cells could result in colonization of recipient testes in cattle of different breeds. Testicular cells were isolated from 8 Bos taurus donor bull calves and then transferred into 15 Bos indicus-cross bull calves. All animals were pre-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 24 publications
(33 reference statements)
4
84
0
3
Order By: Relevance
“…However, in bulls, colonization and full spermatogenesis has been achieved only after autologous transplantation of SSCs (Izadyar et al 2003b). After homologous and heterologous transplantations, full spermatogenesis has not been shown (Izadyar et al 2003b, Herrid et al 2006, probably because stem cells might not survive to an immunological reaction against them, so no or few daughter cells are formed.…”
Section: Discussionmentioning
confidence: 99%
“…However, in bulls, colonization and full spermatogenesis has been achieved only after autologous transplantation of SSCs (Izadyar et al 2003b). After homologous and heterologous transplantations, full spermatogenesis has not been shown (Izadyar et al 2003b, Herrid et al 2006, probably because stem cells might not survive to an immunological reaction against them, so no or few daughter cells are formed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in farm animals, combining male germ cell transplantation with a large-scale culture of SSCs would provide a renewable source of stem cells for transplantation (3). This system has great potential since it provides proper alternatives to artificial insemination (AI) for the use of elite sires in an extensive production system in which AI is more impractical (4). Moreover, SSCs can be utilized in gene transfer to the next generation and this is proved to be more effective and time-saving than other approaches such as the use of embryonic stem cell or nuclear transfer technologies (5).…”
Section: Introductionmentioning
confidence: 99%
“…As reported, SSCs from domestic species could colonize and proliferate in host mouse testes after transplantation, but could not give rise to entire spermatogenesis , Izadyar et al 2002, Oatley et al 2002, Kim et al 2006; Table 2), probably due to the phylogenetic disparity between donors and hosts. Later, allogeneic transplantation of SSCs was tested in boars, bulls, goats, sheep, and dogs (Honaramooz et al 2002a, Izadyar et al 2003, Herrid et al 2006, 2009b, Kim et al 2008, and the development of the donor germ cells was observed in those recipients of homogeneous species ( Fig. 2A and Table 2).…”
Section: Transplantation Of Sscs From Domestic Animalsmentioning
confidence: 99%